Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/olq.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sexually Transmitted Infection Screening and Management in Indiana Community Health Centers

Abstract: It is likely that CHCs are not aware of patient sexual health risks because standard of care screening was observed only for gonorrhea and chlamydia during the first trimester and for syphilis testing when symptoms were present. As CHCs increase their role in preventive care with the implementation of the Affordable Care Act, focus must be upon clinician awareness of patient sexual health and training to identify and manage STIs in their patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Obstetricians-gynecologists and family medicine physicians reported using EPT more often than internal medicine physicians (63,64). A survey of community health centers in Indiana reported that 61% told patients with gonorrhea or chlamydia to refer their partner for testing and treatment and 18% always gave medication to patients to distribute to their partners (66). A survey of Federally Qualified Health Centers in New York City reported that 80% provided EPT for chlamydia, of which 47% were by prescription only, 27% by both prescription and dispensed medication, and 6% by dispensed medication only (67).…”
Section: Current Practice On Selected Clinical Services In the Unitedmentioning
confidence: 99%
“…Obstetricians-gynecologists and family medicine physicians reported using EPT more often than internal medicine physicians (63,64). A survey of community health centers in Indiana reported that 61% told patients with gonorrhea or chlamydia to refer their partner for testing and treatment and 18% always gave medication to patients to distribute to their partners (66). A survey of Federally Qualified Health Centers in New York City reported that 80% provided EPT for chlamydia, of which 47% were by prescription only, 27% by both prescription and dispensed medication, and 6% by dispensed medication only (67).…”
Section: Current Practice On Selected Clinical Services In the Unitedmentioning
confidence: 99%
“…Furthermore, studies have shown that FQHC growth has tended to occur in pre-existing service markets, urban areas, and locales with lower poverty rates, suggesting the influence of market-driven factors [12,48]. Although FQHCs face a number of challenges, a body of research indicates their positive impact on STI care [13,20,21]. In this study, we found FQHC availability to be associated with higher rates of bacterial STIs, and this association persisted even when considering Medicaid expansion-an important driver of health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Standards of care at FQHCs are also important considerations. In a large Midwestern FQHC system, CT and NG screening was only provided upon patients' request or when symptoms were present, despite high community infection rates [21]. In another study of urban FQHCs, patients were not routinely asked about sexual health concerns, regardless of their willingness to engage with providers [22].…”
Section: Federal and State Provisions For Sexual Healthcarementioning
confidence: 99%
See 1 more Smart Citation